Fuel cell systems explained - Larminie, James; Dicks, Andrew (Chichester, West Sussex John Wiley & Sons Ltd., 2003)
The use of fuel cells as independent power sources is expected to become increasingly widespread. This book aids understanding of the technology by setting out the working methods, behaviour, limitations, special features and potential of fuel cells. This edition includes a section on standards within the industry.
Includes bibliographical references and index.
Keywords: Fuel cells